ABOUT HAMLET BY WILLIAM SHAKESPEARE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION Hamlet, written by William Shakespeare, is a timeless masterpiece that has captivated audiences for centuries due to its complex plot, fascinating characters, and profound concepts. This article provides an in-depth examination of Hamlet, delving into its intricate storyline, the motivations of its characters, and the underlying themes it conveys. By carefully analysing the literary aspects and critical views, we reveal the lasting importance and profound influence of Shakespeare’s famous tragedy.